2011
DOI: 10.1111/j.1439-0523.2011.01879.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic linkage map construction for kenaf using SRAP, ISSR and RAPD markers

Abstract: Kenaf (Hibiscus cannabinus L.) is one of the most economically important crops for fibre production. Genetic maps have been developed in almost all the agricultural crops. However, genetic information for kenaf, especially, at the molecular level is limited. To better understand the genetic basis of kenaf for the improvement of production and to lay the foundation for molecular breeding efforts, a primary genetic linkage map was constructed using sequence-related amplified polymorphism (SRAP), inter-simple seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 56 publications
(65 reference statements)
2
9
1
Order By: Relevance
“…In this study, high levels of genetic diversity were found for the various kenaf genotypes. PIC and GD detected in this study for kenaf are higher than those previously observed using other marker (SRAP, ISSR, RAPD and AFLP) systems (Cheng et al 2004;Chen et al 2011;Zhang et al 2013). In additions, these results are higher than the findings of Li et al (2016) in 28 kenaf cultivars using 72 EST-SSR markers.…”
Section: Discussioncontrasting
confidence: 81%
“…In this study, high levels of genetic diversity were found for the various kenaf genotypes. PIC and GD detected in this study for kenaf are higher than those previously observed using other marker (SRAP, ISSR, RAPD and AFLP) systems (Cheng et al 2004;Chen et al 2011;Zhang et al 2013). In additions, these results are higher than the findings of Li et al (2016) in 28 kenaf cultivars using 72 EST-SSR markers.…”
Section: Discussioncontrasting
confidence: 81%
“…The PCR analysis was similar to the analysis of Chen et al. (). All amplified products were segregated on 6% polyacrylamide gels, and after electrophoresis, the gel was stained with AgNO 3 solution.…”
Section: Methodsmentioning
confidence: 57%
“…To add a large number of DNA markers and thus saturate our map, we utilized combinations of primers rather than a single primer in RAPD reactions, as reported by Chen et al. (). Although we attempted to add the molecular markers, the absence of a large amount of molecular markers made the reduction in the jute LG number impossible at present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations